Molecular investigation of the effect of weightlifting training on helper T cell subsets in female weightlifting athletes: an immune profiling panel - Duran, T.; Karaselek, M. A.; Kuccukturk, S. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: In this study, it was aimed to molecularly investigate the changes in the helper T (Th) cell subgroups of intense weightlifting training. For this purpose, transcription factor and cytokine expressions of Th1, Th2, Th17, and regulator T cell (Treg) cells were evaluated. METHODS: Eight elite weightlifting athletes were included in the study. Within the scope of the study, transcription factor and cytokine expressions of Th cell subgroups were evaluated by real-time polymerase chain reaction (qPCR) method before training, after intense training with 90-100% capacity, and after 120 minutes of rest from training. RESULTS: As a result of the study, when the pre-training and post-training expressions were compared, an increase in Th1 and Th2 cell factors and a decrease in Th17 and Treg cell-related expressions were detected. These changes were statistically significant (P<0.05). The changes in expressions after training and after 120 minutes of rest were not statistically significant (P>0.05). CONCLUSIONS: Changes have been detected in Th cell subgroups due to intense weightlifting training, and these changes are the first study conducted with female weightlifters.